Downdraft gasifier Imbert type and clean-up system design, for small scale power generation using biomass - Mendonça, Miguel (2022)
This paper presents a prototype of fuel gas generation system from biomass gasification. It comprises the small scale downdraft gasifier and the gas cleaning system aiming the generation of combustible gas (producer gas) suitable to run the internal combustion engine. This work is part of a project concerning the development of a compact power generation equipment, which aims the valorization of forest and rural waste, constituting an incentive to reduce fuel load available in those places, and thereby contributing to reduce fire hazard (SUBe project). The system is required to be small,easy to carry and install. The design methodology available in the literature for downdraft gasifiers applies to gasifiers larger than intended. Thus, the design of the gasifier was performed by extrapolation of information in literature for larger gasifiers. The producer gas obtained from gasification contains to high levels of impurities, such as tars and particulate matter, to be used as internal combustion engine fuel; they cause rapid engine degradation, and so need to be removed. A clean-up system was proposed in three stages: in first instance a hot gas clean-up using a cyclone designed to eliminate particles and compounds; then a heat exchanger is placed in order to cool the gas to around 60 °C in order to condensate tars and water; finally a cold gas clean-up phase using two filters one with organic material (biomass) and the other with a special fabric filter.